Does autologous blood transfusion during liver transplantation for hepatocellular carcinoma increase risk of recurrence? - Araujo, Raphael LC (World J Gastrointest Surg, 2016)
AIM: To analyze outcomes in patients who underwent liver transplantation (LT) for hepatocellular carcinoma (HCC) and received autologous intraoperative blood salvage (IBS). METHODS: Consecutive HCC patients who underwent LT were studied retrospectively and analyzed according to the use of IBS or not. Demographic and surgical data were collected from a departmental prospective maintained database. Statistical analyses were performed using the Fisher’s exact test and the Wilcoxon rank sum test to examine covariate differences between patients who underwent IBS and those who did not. Univariate and multivariate Cox regression models were developed to evaluate recurrence and death, and survival probabilities were estimated using the Kaplan-Meier method and compared by the log-rank test. RESULTS: Between 2002 and 2012, 158 consecutive patients who underwent LT in the same medical center and by the same surgical team were identified. Among these patients, 122 (77.2%) were in the IBS group and 36 (22.8%) in the non-IBS group. The overall survival (OS) and recurrence free survival (RFS) at 5 years were 59.7% and 83.3%, respectively. No differences in OS (P = 0.51) or RFS (P = 0.953) were detected between the IBS and non-IBS groups. On multivariate analysis for OS, degree of tumor differentiation remained as the only independent predictor. Regarding patients who received IBS, no differences were detected in OS or RFS (P = 0.055 and P = 0.512, respectively) according to the volume infused, even when outcomes at 90 d or longer were analyzed separately (P = 0.518 for both outcomes). CONCLUSION: No differences in RFS or OS were detected according to IBS use. Trials addressing this question are justified and should be designed to detect small differences in long-term outcomes.